Global Media and Cultural Identity: Opportunities and challenges for Morocco in the Digital Era - FERRATI, Abdesselam (International Journal of Language and Literary Studies, 2021)
Anthropologists and media analysts have long recognized the Internet and satellite channels as some of the most powerful tools that add tremendous value to the knowledge and experiences of youth. A common interpretation of this idea is that new media technologies have become an important source for information, news updates, cross-cultural communication, socializing, and entertainment. The effects of these tools on young people have predominantly been studied with respect to academic as well as health features. Drawing on data from a survey capturing the digital behaviors of Moroccan students, this article complements previous studies by examining the impact of Internet and satellite channels on the behaviors of Moroccan students. It explores the implicit and denotative consequences of modern media upon the values, behaviors, and lifestyles of young Moroccans. Further, the paper addresses the effects of the massive dissemination of global cultural products on teenagers’ attitudes towards their cultural values. Additionally, the research assumes that inducing behavioral change is overlooked once media outlets start demonizing the uniqueness of local cultures, thus ignite resistance to unconventional values among youth.